Comparative study of yeast selenium vs. sodium selenite on growth performance, nutrient digestibility, anti-inflammatory and anti-oxidative activity in weaned piglets challenged by Salmonella typhimurium. Issue 4 (May 2020) - Lv, Liangkang; Zhang, Hui; Liu, Zhengya; Lei, Long; Feng, Zhi; Zhang, Dandan; Ren, Ying; Zhao, Shengjun
The present study was conducted to investigate the effects of dietary supplementation of selenium from different sources on the growth performance, nutrient digestibility, and blood immune indices of piglets orally challenged with Salmonella typhimurium (ST). In a 2 × 2 factorial arrangement, 32 piglets (6.43 ± 0.54 kg of body mass) were assigned into four groups with or without dietary inclusion of sodium selenite (SS) or yeast selenium (YS) and with or without ST challenge (5 ml 1 × 10 9 cfu/ml ST or 5 ml saline) on d 13. In each period, YS increased average daily feed intake and average daily gain but did not reach statistical significance. During the challenged stage, piglets fed YS had higher digestibility of dry matter, crude protein, crude fat, and YS reduced the amount of Escherichia coli in feces. Additionally, YS regulated the composition of T-lymphocyte subset and influenced the production of inflammatory cytokines. In conclusion, in this study selenium-enriched yeast was more effective in enhancing nutrient digestibility, and inhibiting inflammation and oxidative stress by inducing the activity of the lymphocytes, expression of antioxidant enzymes and so on.